PENGARUH MODELPEMBELAJARANPROBLEM BASED LEARNING(PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Sri wahyuningsih; Anim Anim (Universitas Asahan, 2019)
The purpose of this study is to determine whether there is influence inusing Problem Based Learning (PBL) model on the students mathematical problem solving ability in opportunity material class X of SMKS Abdi Negoro in the academic year2018/2019. This type of research is quasi-experimental research design with two group pre-test and posttest. The population in this study was all classX consisting of 6 class. The reseearch sample consisted of 2 classes (class X TKJ 1 and TKJ 2) which were taken by cluster random sampling. In class X TKJ2 as control class using the Direct Teaching model and in class X TKJ1 as an experimental class using the Problem Based Learning (PBL) model. After learning was given,posttest was obtained with the result of the experimental class average 84,00 and the control class was 78,73. The result of ttestwas obtained that t_count = 2,49> t_table = 1,67 then Ha was accepted.Thus,there is effect of Problem Based Learning (PBL) modelon student’s mathematical problem solving ability in opportunity materialat class X of SMKSAbdi Negoro.Keywords: Model Problem Based Learning (PBL), Direct Teaching model, Opportunity.